Optimalisasi Penerimaan PBB-P5L Sektor Minerba melalui Analisis Proses Bisnis pada KPP Pratama Batulicin - Bagus Dwi Septian; Diva Noviandani; Granatabror Marzuq Mushoddaq; Muhammad Islam Izzatii; Yuni Rahma Khoirunnisa (Jurnal Riset Perpajakan: Amnesty, 2026)
This study investigates the Business Process of Land and Building Tax (PBB-P5L) in the mining sector (minerba) at KPP Pratama Batulicin, focusing on the challenges that hinder optimal tax revenue collection. The primary objective is to examine how well the tax process operates, identify issues related to tax administration, and assess the untapped tax potential. Using a qualitative descriptive approach, the study analyzes secondary data from KPP Pratama Batulicin and external sources, including data on mining permits (IUP/IUPK) and tax compliance. Data collection was done through document analysis, with a focus on mining tax registration, reporting, and assessment procedures. The findings reveal significant discrepancies between the number of mining permit holders and registered taxpayers, as well as data inaccuracies that prevent effective tax collection. The estimated untapped tax potential before audits was Rp30.87 billion, increasing to Rp38.59 billion after audits, indicating a significant underreporting of taxable assets. The study suggests improvements in data integration between DJP and ESDM, the use of satellite imagery for land monitoring, and the implementation of a risk-based oversight system. These recommendations are expected to improve data accuracy, reduce the tax gap, and enhance PBB-P5L revenue collection, offering valuable insights for policymakers and tax practitioners aiming to optimize tax administration in the mining sector.